1960
DOI: 10.1103/physrevlett.5.258
|View full text |Cite
|
Sign up to set email alerts
|

Possible Anomaly in Meson Production inp+dCollisions

Abstract: Several authors have proposed the existence of new particles and n -n resonances. 1 " 5 Along these lines we are studying the reactions p + d-+\ p + d-~ < He 3 + 77° He 3 + a; 0 He 3^-^4 "^^1" He 3 + 7r°+7r°

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
1

Year Published

1964
1964
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(95 citation statements)
references
References 8 publications
5
89
1
Order By: Relevance
“…This phenomenon, which was observed also in the fusion reactions to d and 4 He -if the produced pion pair was isoscalar -did not ¿nd a satisfactory theoretical explanation so far. Hence it was called just after the initials of the authors Abashian, Booth and Crowe, who were the ¿rst to reported about this effect [27].…”
Section: Towards the ¿Rst Non-trivial Dibaryonmentioning
confidence: 99%
“…This phenomenon, which was observed also in the fusion reactions to d and 4 He -if the produced pion pair was isoscalar -did not ¿nd a satisfactory theoretical explanation so far. Hence it was called just after the initials of the authors Abashian, Booth and Crowe, who were the ¿rst to reported about this effect [27].…”
Section: Towards the ¿Rst Non-trivial Dibaryonmentioning
confidence: 99%
“…These include studies in pion-proton [1] and proton-proton collisions [2], as well as in the pd → 3 He ππ [3,4,5] and dd → 4 He ππ [6,7,8] reactions. For excess energies Q below about 100MeV one sees no sign of the low mass s-wave ππ enhancement, known as the ABC effect [9], and the maxima in the invariant mass distributions tend more to be pushed to the highest possible values.…”
Section: Introductionmentioning
confidence: 99%
“…Initially the low-mass enhancement had been interpreted as an unusually large ππ scattering length and evidence for the σ meson, respectively [1]. Since the effect showed up particularily clear at beam energies corresponding to the excitation of two ∆s in the nuclear system, the ABC effect was interpreted later on by a t-channel ∆∆ excitation in the course of the reaction process leading to both a lowmass and a high-mass enhancement in isoscalar M ππ spectra [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The ABC effect -a strong and intriguing low-mass enhancement in the ππ invariant mass spectrum -is known from inclusive measurements of two-pion production in nuclear fusion reactions to the few-body systems d, 3 He and 4 He [1][2][3][4][5][6][7][8][9][10][11]. Its explanation has been a puzzle for 50 years now.…”
Section: Introductionmentioning
confidence: 99%